Creative Ice Cream Experiment Using the Freezing Point Depression Principle - Safitri, Wulan Dwi; Wardana, Dian; Ramadhan, Dwi Sapri; Fahmi, Jaman; Zubir, Moondra; Siregar, Koriatul Jannah; Purba, Sunita Karin; Siregar, Nurdin (Universitas Negeri Medan, 2025)
This research aims to explore creative approaches in ice cream production by utilizing the effect of freezing point depression. Through these experiments, we employed various additives that influence the physical properties of ice cream, resulting in a final product that is softer, creamier, and able to maintain optimal texture at different temperatures. The experimental method involved varying the types of additives combined with the base ice cream mixture. The measured parameters included freezing point depression, texture, and softness of the produced ice cream. The collected data were analyzed to determine how each additive affected the physicochemical characteristics of the product. The results showed that differences in sugar content among the ingredients significantly influenced the degree of freezing point depression in the ice cream.